An evolutionary consideration of stress response, biodiversity, and anthropogenic context - Sharpe, Sam Lipson (Kansas State University, 2024)
Variation is inherent in nature and underlies all evolutionary processes, with organismal diversity representing both a response to and a prerequisite for these processes. This dissertation considers fundamental concepts of evolutionary biology, including biodiversity, categorization of similarity and difference, and environmental heterogeneity, against the backdrop of profound threats to ecological diversity and marginalized human populations due to anthropogenic activities. In this way, evolutionary considerations of biodiversity in the Anthropocene epoch occur at the interface of nature and culture and can be understood through Donna Haraway’s term natureculture. My research uses a naturecultural framework to investigate stress response across populations of a wild plant species and explore strategies for improving representation and inclusion of sex, gender, and sexuality diversity in biology classrooms. To assess how local adaptation can impact physiological and transcriptomic responses to anthropogenically mediated sources of abiotic stress, I utilized climatically diverse populations of the wild foxtail millet, Setaria viridis. This species has many advantageous qualities as a model system, including widespread populations across a range of habitats, high genetic diversity, short generation times, small size, high rates of self-pollination, copious seed production, and a relatively small, sequenced diploid genome. Using 9 populations of S. viridis from geographically and climatically diverse home ranges, I compared photosynthetic response to drought stress in a greenhouse dry down experiment. With a subset of these populations, I assessed root surface area, aboveground biomass, and sensitivity to drought stress across plants of different ages. I found significant differences in drought tolerance by population which was not correlated with climate of origin but may be partially explained by differences in total plant size and ratio of root surface area to aboveground biomass. For S. viridis plants within the same population, plant age at the start of drought impacted both overall drought sensitivity and total production of inflorescences. To further address questions of local adaptation and abiotic stress response, I selected 2 S. viridis populations that demonstrated divergent physiological responses to drought stress and compared transcriptomic response across drought, chilling, and salinity stress conditions. I found substantial variability in the number and function of genes significantly up or down regulated between populations and treatment conditions, with only a few genes and gene functions showing similar response patterns across both populations or multiple stress conditions. There was, however, notable alignment of differently expressed genes from both S. viridis populations with a database of nearly 200 molecularly characterized drought tolerance genes. In an additional consideration of diversity, interface between science and culture, and anthropogenically mediated stress and resilience, I explored current issues in biology education that exclude or mischaracterize sex, gender, and sexuality diversity, and discussed emerging alternate pedagogical strategies for increasing inclusivity. I drew parallels between the oversimplified presentations of sex across taxa as a universal male/female binary in many biology classrooms, the ongoing social, legal and medical harms faced by queer, transgender, and intersex people, and the use of appeals to just such a universal sex binary to justify and perpetuate these harms. Importantly, biology education also offers many powerful opportunities to challenge such harmful misconceptions through providing more comprehensive, nuanced, and inclusive conceptualizations of sex, gender, and sexuality diversity across the tree of life. Through the integration of evolutionary, ecological, genomic, pedagogical, and naturecultural approaches, the research presented in this dissertation has important implications for understanding biodiversity, stress response, and resilience to anthropogenic contexts for human and non-human organisms.
Keywords: Evolution; Ecological genomics; Plant biology; Inclusive pedagogy; Sex diversity; LGBTQIA+ biology